2016
DOI: 10.1097/01.nep.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Using Simulation to Improve Student and Faculty Knowledge of Telehealth and Rural Characteristics

Abstract: The purpose of this study was to evaluate the knowledge of senior baccalaureate nursing students and faculty members regarding telehealth and rural nursing concepts before and after participation in a newly developed simulation, which incorporated telehealth use in a rural home environment. Statistically significant increases in knowledge were found in both faculty and students following participation in the simulation. The results of this research indicate the need to increase student and faculty knowledge ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Simulation allows training content to be easily tailored to differing objectives and desired outcomes associated with undertaking virtual visits in diverse home healthcare services [ 43 ], a training concern that some of the participants reflected on. While there is growing indication that simulation may be a valuable means of teaching telecare practice to qualified healthcare professionals [ 60 ] as well as nursing students [ 40 , 61 63 ], the potentials in using simulation in vocational telecare training for home healthcare staff remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation allows training content to be easily tailored to differing objectives and desired outcomes associated with undertaking virtual visits in diverse home healthcare services [ 43 ], a training concern that some of the participants reflected on. While there is growing indication that simulation may be a valuable means of teaching telecare practice to qualified healthcare professionals [ 60 ] as well as nursing students [ 40 , 61 63 ], the potentials in using simulation in vocational telecare training for home healthcare staff remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…As found in previous research, the scores indicated that our students found the newly developed simulation-based learning experience satisfying and confidence building (Merritt et al, 2018; Quinlin et al, 2020). As reported in previous studies (Mennenga et al, 2016; Merritt et al, 2018; Mulcare et al, 2020; Quinlin et al, 2020), our students offered comments that the simulation experience would be helpful in future clinical practice.…”
Section: Discussionmentioning
confidence: 86%
“…Lister et al (2018) 29 and List et al ( 2019) 30 through modifying their nursing curriculum to include telehealth, demonstrated that even small modifications to the existing curriculum can improve student confidence in this aspect of their practice. Other nursing programmes incorporating telehealth simulation have also demonstrated improvement knowledge gain through this adaptation of curriculum 31 . Rutledge et al, 6 based on their experience, outline a range of comprehensive topics and techniques which they advocate including in telehealth nursing curriculum.…”
Section: Nurse Trainingmentioning
confidence: 99%